332. Metastatic bone volume dose estimation procedure in 223Ra-Xofigo treatments. (December 2018) - Ostinelli, A.; Duchini, M.; Cacciatori, M.; Frigerio, M.; Frigerio, G.
Abstract : Purpose: 223Ra-dichloride (BAYER Xofigo) radiometabolic therapy of bone metastatic lesions of castration-resistant prostate cancer seems to offer a valid alternative to conventional approaches, due to the alpha particles emitted in the tumor site. While a specific approach was developed to identify proper criteria for the morpho-functional assessment of activity distribution, a further step is needed to evaluate the local dose. Methods: Preliminary gamma-camera calibrations (sensitivity and transmission curves) for 223Ra were performed. After estimating the metastatic activity and volume through scintigraphic images, the target absorbed dose is given by the ratio between energy and mass. While the latter can be evaluated from the same images, the local energy depends on the physical characteristics of the emitted radiation and the cumulated activity. In this way, both the energy per Bq released by each radiation type and its fraction locally deposited can be calculated. Cumulated activity requires data on the Xofigo kinetics over time, available in literature. Results: Starting from the relative radiation emissions by 223Ra, 219Rn, 211Po, 211Bi and 207Tl the following MeV/Bq values were obtained: 26.3 alpha (95.33%), 1.0 beta (3.64%) and 0.3 X and gamma (1.03%). While charged particles energies are completely released to the biological mass, tissue absorption coefficients and target thickness must be considered for photons. By applying these criteria to a 118 cm 3 metastatic localization, a 0.35 MBq initial activity and a 4.73d effective half-life (see table and figures), the 6.7 Gy dose was obtained. This value concerns a Xofigo single dose administration and should be reconsidered for the entire treatment cycle. Conclusions: The previous results are consistent with the literature. Their main advantage is the possibility to obtain immediate dose estimates, if the bone metastasis volume and its localized activity and time evolution are known. The experimental uncertainty is mainly related to volume and density of the metastatic tissue.